Prostaglandin I2 (prostacyclin). - Kelton, J. G. (1980)
Prostaglandin I2 (PGI2), or prostacyclin, is a recently discovered prostaglandin that affects many organ systems. It is both a potent inhibitor of platelet aggregation and a powerful vasodilator. The recent demonstration that it is the main prostaglandin synthesized by the blood vessel wall suggests that it may play an important role in limiting platelet-mediated thrombosis. However, despite considerable investigation, the exact physiological role of PGI2 has yet to be elucidated.